Cultural Ambassadorship in the Digital Age: Storytelling Sustainable Tourism through Social Media - Wulan Yulianti; Janette Maria Pinariya; Salsabila Tiara Saputri; Dhita Widya Putri (Ikatan Sarjana Komunikasi Indonesia, 2026)
Tourism communication increasingly relies on digital platforms to promote sustainability and cultural identity. Beauty pageant titleholders, often positioned as cultural ambassadors, play a unique role in this process. This study explores how cultural ambassadors construct narratives of sustainable tourism through their social media presence. Using a qualitative approach, the research relies on in-depth interviews with selected pageant representatives to understand their experiences, strategies, and intentions in employing digital storytelling. Findings reveal that titleholders utilize social media not only to showcase destinations but also to embed messages of cultural preservation, environmental responsibility, and community empowerment. Social media platforms become extensions of their ambassadorship, allowing them to frame personal stories and advocacy in ways that engage diverse audiences. The study concludes that digital storytelling, as practiced by cultural ambassadors, bridges individual identity and collective responsibility in tourism communication. This contributes to a deeper understanding of how personal narratives intersect with sustainability discourses in the digital era.